Use of molnupiravir in patients who developed SARS-CoV2-Infection during hospitalization - Telli Dizman, Gülçin; Çakır, Yahya; Korubük, Gamze; Metan, Gökhan; Ünal, Serhat (Acta Medica, 2023)
Background: Molnupiravir is an oral anti-viral that inhibits SARS-CoV-2 replication and reduces viral load. We aimed to investigate mortality rates and the factors affecting mortality in patients receiving molnupiravir who were hospitalized for reasons other than COVID-19 in a tertiary care university hospital. Methods: Patients who received molnupiravir for COVID-19 according to Turkish Ministry of Health guidelines and were hospitalized for reasons other than COVID-19 were included in the study. Demographic and clinical characteristics of patients were compared according to survival status defined as 30-day mortality. Results: The mortality rate of 101 patients with Covid-19 was found to be 6.93 %. The rates of corticosteroid use, oxygen support, and mechanical ventilation requirement were significantly higher in patients who died within 15 days of the PCR positivity. Although not statistically significant, the ratio of concomitant bacterial pneumonia was higher in patients who did not survive. Also, the mortality rate was lower in patients who were vaccinated three doses or more without statistical significance. Conclusion: In patients who were hospitalized for other reasons and received molnupiravir treatment with a diagnosis of COVID-19, the development of respiratory failure was the only demographic factor that was statistically different in terms of mortality.